Assessment by Thai academic English writing teachers of the flow of given to new topic information within academic writing - David D. Perrodin (Journal on English as a Foreign Language, 2021)
Adhering to a structured process of the flow of given to new topic information within academic written discourse is a significant challenge for most tertiary-level non-native EFL students. The progression of given to new topic information in written academic text is equally difficult for many non-native academic English writing teachers to distinguish, much less assess. This research seeks to determine if given to new information progression can be significantly identified, and explore the possibility of such topic progression being utilized as a practical form of academic writing assessment by experienced Thai tertiary teachers of academic English. Multiple Linear Regression was employed to determine the relationship between the Thai writing teachers' identification of the flow of given to new topic information and a preliminary analysis of topic information flow by a qualified native English writing teacher. The insights gained from this study show that the Thai academic English writing teachers could not significantly detect the presence of given to new topic information progression within the academic texts. The implication of this research suggests that at this time, the practical utilization of a given to new progression analysis may not be a feasible evaluative measure in written assessments for Thai academic English writing teachers.